3D ZnO/Au/CdS Sandwich Structured Inverse Opal as Photoelectrochemical Anode with Improved Performance. Issue 18 (1st October 2015) - Li, Cheng; Zhu, Xiuting; Zhang, Haifeng; Zhu, Zhichao; Liu, Bo; Cheng, Chuanwei
Abstract : Photoelectrochemical water splitting: A novel 3D ZnO/Au/CdS sandwich structured inverse opal photoanode is designed for a photoelectrochemical water splitting application with improved performance.